Complications and predisposing factors from a decade of total laryngectomy. Issue 3 (21st March 2020) - Thompson, C S G; Asimakopoulos, P; Evans, A; Vernham, G; Hay, A J; Nixon, I J
Abstract: Background: Total laryngectomy is often utilised to manage squamous cell carcinoma of the larynx or hypopharynx. This study reports on surgical trends and outcomes over a 10-year period. Method: A retrospective review of patients undergoing total laryngectomy for squamous cell carcinoma was performed ( n = 173), dividing patients into primary and salvage total laryngectomy cohorts. Results: A shift towards organ-sparing management was observed. Primary total laryngectomy was performed for locoregionally advanced disease and utilised reconstruction less than salvage total laryngectomy. Overall, 11 per cent of patients developed pharyngocutaneous fistulae (primary: 6 per cent; salvage: 20 per cent) and 11 per cent neopharyngeal stenosis (primary: 9 per cent; salvage: 15 per cent). Pharyngocutaneous fistulae rates were higher in the reconstructed primary total laryngectomy group (24 per cent; 4 of 17), compared with primary closure (3 per cent; 3 of 90) ( p = 0.02). Patients were significantly more likely to develop neopharyngeal stenosis following pharyngocutaneous fistulae in salvage total laryngectomy ( p = 0.01) and reconstruction in primary total laryngectomy ( p = 0.02). Pre-operative haemoglobin level and adjuvant treatment failed to predict pharyngocutaneous fistulae development. Conclusion: Complications remain hard to predict and there are continuing causes of morbidity. Additionally, prior treatment continues to affect surgical outcomes.